Numerical investigation of quasi-static bubble growth and detachment from submerged orifices in isothermal liquid pools: The effect of varying fluid properties and gravity levels. (September 2015) - Georgoulas, A.; Koukouvinis, P.; Gavaises, M.; Marengo, M.
Highlights: Validation of an improved VOF model for bubble growth from submerged orifices. Conduction of a wide range of parametric numerical experiments. Investigation of the effect of fluid properties on bubble growth and detachment. Investigation of the effect of gravity on bubble growth and detachment. Abstract: The present investigation, identifies the exact quantitative effects of fundamental parameters, on the detachment characteristics of isolated bubbles, emanating quasi-statically from submerged orifices into isothermal liquid pools. For this purpose, a Volume of Fluid (VOF) based interface capturing approach is further improved, for the conduction of axisymmetric and 3D numerical experiments on adiabatic bubble growth dynamics. The predictions of the model, are quantitatively validated against literature available experimental data, showing excellent agreement. Two series of numerical experiments are performed, quantitatively exploring the parametric effects of the liquid phase properties in five different gravity levels, and the effect of the gravity vector direction inclination angle, respectively. It is found that the bubble detachment characteristics, are more sensitive in the variation of the surface tension, liquid phase density and gravity, while the effect of liquid phase dynamic viscosity is generally minimal. From dimensionless analysis, two correlations are derived, which for the examined range of Eötvos numbers, are able to predict the equivalent bubble detachment diameter and the bubble detachment time, respectively. It is also found that the bubble detachment characteristics, reduce significantly as the gravity vector direction gradually deviates from being parallel to the bubble injection orifice, following a non-linear decrease.